Surveillance of primary dentition caries in Germiston, South Africa, 1981–97 - Cleaton-Jones P, Williams S, Fatti LP (Blackwell Synergy, 2000)
This 17-year-long study examined trends of dental caries rates in the primary dentition of 6843 preschool children in a South African city. Methods: Calibrated dentists did repeated cross-sectional epidemiological surveys of dental caries in 2- to 5-year-old nursery school children using WHO diagnostic criteria between 1981 and 1997. Results: Both the percentage of children with dmft±0 and mean dmft increased between 1981 and 1989 and have slowly de- Key words: Africa; caries; diagnosis; epidemiology clined ever since in the absence of organised prevention to produce a secular trend of decreasing caries rates.